Validity of patient-reported information: agreement rate between patient reports and registry data - Tomone Watanabe; Yuichi Ichinose; Tsutomu Toida; Takahiro Higashi (BMC Health Services Research)
Abstract Background The accuracy of patient-reported clinical information, including cancer stage, is not well understood. This study aims to evaluate the agreement between patient-reported survey data and clinical information recorded in hospital-based cancer registries (HBCR). Methods A total of 730 patients from 166 hospitals in Japan were randomly selected and informed that their survey responses would be validated against HBCR data. Demographic details, including age, sex, cancer stage, and cancer site, were recorded and compared with clinical data from the HBCR. Agreement rates between patients’ self-reported demographic and clinical data and the corresponding HBCR records were analyzed. Logistic regression analysis was conducted to identify factors associated with accurate reporting of cancer stage information. Results Agreement rates for age, sex, and cancer site were 99.4%, 99.8%, and over 90% across all cancer sites, respectively. The agreement rate for cancer stage reporting was 49.9%. Patients with stage IV cancer had the highest agreement rate at 68.4%. Patients under 75 years of age and those with specific cancer types demonstrated higher odds of reporting data consistent with HBCR records. Conclusions For cancer stage data, relying on more credible sources, such as cancer registries, is recommended over patient-reported information to ensure accuracy.